Criteria for assessing the health status of middle-aged women - Shlapak, A.A.; Vinokurova, K.R.; Zaharova, A.V. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to identify the characteristics of age-related physiological changes in women's body systems in each decade of middle age in order to substantiate the criteria for the health improvement of middle-aged women. Methods and structure of the study. To identify the criteria for recovery, we used scientometric analysis of age-related physiological changes in women's bodies. Results and conclusions. Scientometric analysis has shown a decline in the adaptive capacity of the cardiovascular system and external respiration function after the age of 40. In addition, after the age of 45, there is a decrease in muscle mass and bone mineral density. Women's postural balance also deteriorates after the age of 40. Assessment of the condition of the cardiorespiratory system, postural balance, and body composition analysis are criteria for the physical health of women in their second mature age. Health-improving physical culture measures can have a positive effect on these criteria.